2010
DOI: 10.1007/s11284-010-0762-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenolic compounds and the effects of invasive and native species in East Asia: support for the novel weapons hypothesis

Abstract: One prediction of the novel weapons hypothesis (NWH) for the dominance of exotic invasive plant species is that the allelopathic effects of successful invaders will, in general, be more biochemically inhibitory to native species and microbes in invaded regions than the native plants themselves. However, no study has compared biochemical concentrations, compositions, or effects of large numbers of native species to those of large numbers of invasive species. In this context we tested the allelopathic and antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…It is unknown how non-water-soluble might influence cooccuring species. Other studies have reported similar results for biogeographic differences in allelopathic effects as a mechanism for the dominance of invasive plant species in their non-native ranges (Callaway and Aschehoug 2000;Callaway and Ridenour 2004;Lankau et al 2004;Wikström et al 2006;Callaway et al 2008;He et al 2009;Thorpe et al 2009;Schaffner et al 2010;Colvin and Gliessman 2011;Inderjit et al 2011a, b;Kim and Lee 2011;Svensson et al 2013) also see meta-analyses by (Lamarque et al 2011;Jeschke et al 2012).…”
Section: Discussionmentioning
confidence: 53%
“…It is unknown how non-water-soluble might influence cooccuring species. Other studies have reported similar results for biogeographic differences in allelopathic effects as a mechanism for the dominance of invasive plant species in their non-native ranges (Callaway and Aschehoug 2000;Callaway and Ridenour 2004;Lankau et al 2004;Wikström et al 2006;Callaway et al 2008;He et al 2009;Thorpe et al 2009;Schaffner et al 2010;Colvin and Gliessman 2011;Inderjit et al 2011a, b;Kim and Lee 2011;Svensson et al 2013) also see meta-analyses by (Lamarque et al 2011;Jeschke et al 2012).…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, this paper provides a basis for studies that explore the changes that allelochemicals may cause in chemical, physical and biological soil properties. Such alterations have been documented as part of the competitive abilities of invasive species in their non-native range (Jordan et al 2008, Kim & Lee 2011, Steinlein 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Many exotic plants possess secondary compounds that are novel to the native community (Callaway & Ridenour, 2004;Macel, Vos, Jansen, Putten, & Dam, 2014). These novel compounds are known to be extremely bioactive (Cappuccino & Arnason, 2006), inhibiting the growth of both native plants and phytoplankton competitors (Hilt & Gross, 2008) and, thus, improving the fitness of invasive species and providing them with a strong competitive advantage over native species (Callaway & Ridenour, 2004;Kim & Lee, 2011). A better understanding of the phytoplankton sensitivity to invasive macrophyte allelochemicals would help explain the patterns of phytoplankton succession in invaded areas.…”
Section: Introductionmentioning
confidence: 99%